PENERAPAN INTERNET OF THINGS PADA STOP KONTAK LAMPU BERBASIS ARDUINO - M Abu Jihad; Yulina Yulina; Sigit Gunanto (STMIK Dian Cipta Cendikia Kotabumi, 2022)
Lighting is a device that is in a house or building that has a function as lighting. The lamp works in the presence of a power source by using a switch to turn it on or off. The problem that often occurs in controlling the lights manually is the difficulty in controlling the lights in remote rooms with a large number of rooms and lights so that the control system is not effective and efficient. Today, Internet of Things has become a popular term to describe a scenario where Internet connectivity and computing capabilities extend to a wide variety of objects, devices, sensors, and everyday items. In this design using this control is done wirelessly via a bluetooth module as a communication medium. To turn on the light, the android smartphone will send a command to the Arduino microcontroller via Bluetooth communication so that the light will turn on according to the command from the Android smartphone. One of the methods used is the Prototype Method which serves as an initial version of the system. After testing, the process of sending and receiving data on the light on-off command is able to work at a distance of approximately 10 meters. With these results, controlling an Android smartphone can be used as a control for lighting lights in a house wirelessly with a distance of approximately 10 meters..